2020
DOI: 10.1038/s41598-020-79863-1
|View full text |Cite
|
Sign up to set email alerts
|

Identification of single motor units in skeletal muscle under low force isometric voluntary contractions using ultrafast ultrasound

Abstract: The central nervous system (CNS) controls skeletal muscles by the recruitment of motor units (MUs). Understanding MU function is critical in the diagnosis of neuromuscular diseases, exercise physiology and sports, and rehabilitation medicine. Recording and analyzing the MUs’ electrical depolarization is the basis for state-of-the-art methods. Ultrafast ultrasound is a method that has the potential to study MUs because of the electrical depolarizations and consequent mechanical twitches. In this study, we evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
119
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 44 publications
(132 citation statements)
references
References 43 publications
3
119
0
Order By: Relevance
“…Previous reports in literature showed that the analysis of the TVS of muscle cross section allows quantification of the deep-superficial movements of bundles of contracting fibers 30 , 31 , 33 . Here we computed the TVS along the US beam axis from radio frequency (RF) signals through autocorrelation in the time (pulse transmissions) and space (depth samples) dimensions 36 .…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Previous reports in literature showed that the analysis of the TVS of muscle cross section allows quantification of the deep-superficial movements of bundles of contracting fibers 30 , 31 , 33 . Here we computed the TVS along the US beam axis from radio frequency (RF) signals through autocorrelation in the time (pulse transmissions) and space (depth samples) dimensions 36 .…”
Section: Methodsmentioning
confidence: 99%
“…Then, the temporal evolution of each pixel was high pass filtered at 5 Hz (4th order Butterworth filter) to attenuate slow movements not associated with muscle contraction 31 . Afterwards, the smoothed TVS was processed by sliding a ROI 33 of 12 × 12 mm over the full image (40 × 40 mm) (Fig. 1 d).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations